(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Chronic diffuse liver lesions are a significant medical and social problem characterized by systemic effects on the body, including organs and tissues of the oral cavity. In recent years, there has been increasing interest in studying the relationship between liver pathology and dental status, due to common pathogenetic mechanisms, including immune, metabolic, and vascular disorders. The purpose of this review article is to analyze current data on the impact of chronic diffuse liver diseases on the oral cavity and substantiate the need for an integrated diagnostic approach. Clinical manifestations, pathogenetic mechanisms, features of the dental status in chronic hepatitis and cirrhosis of the liver, as well as modern diagnostic methods and interdisciplinary interaction are considered. It has been shown that the progression of liver pathology is accompanied by a deterioration in dental parameters, which requires the integration of efforts of dentists and general practitioners.